Hyperthermic intraperitoneal chemotherapy: Ideal and reality - Fan-He Dong; Yu-Qiang Shan; Wen-Cheng Kong; Hao-Ran Wei; Lin-Po Zhou; Ye-Bin Yang; Jing Shi; Cheng-Hao Ji; Yi-Jia Zhang (Asian Journal of Surgery)
Hyperthermic Intraperitoneal Chemoperfusion (HIPEC) is a new adjuvant therapy for the treatment of abdominal malignant tumors and metastases, which has shown great potential. The HIPEC technique can effectively kill residual lesions in the abdominal cavity through the synergistic sensitization effect of thermal chemotherapy and the circulating perfusion and washing effect of large volume perfusion fluid, thereby reducing the occurrence of malignant ascites and reducing the risk of postoperative recurrence and metastasis. However, there are still many problems in the practical operation of HIPEC, such as non-uniform distribution of perfusate temperature, inadequate perfusion due to the presence of ‘dead space’, incomplete cytoreductive surgery (CRS), instances of catheter obstruction during perfusate circulation, the lack of a uniform standard for selecting appropriate HIPEC techniques, occupational exposure of medical personnel during the HIPEC procedure, and the selection of HIPEC chemotherapy regimens for patients with various types of tumors. This article aims to summarize the problems encountered in the clinical practice of HIPEC, explore the problems that can be improved, and put forward some suggestions, so as to promote the further standardization and normalization of HIPEC technology.